An Application of Compositional Metafunctions in Improving Children’s Ability to Learn English Through Images - Ngongo, Magdalena; Purba, Ridwin; Thao, Nguyen Van; Herman, Herman (Jurnal Pendidikan Progresif, 2022)
An Application of Compositional Metafunctions in Improving Children’s Ability to Learn English Through Images. Objectives: The purpose of this study was to access the application of compositional metafunctions in improving children’s ability in learning English through images. Methods: The method used in this study is a qualitative approach with a literature review using sources from the internet, books, and related research outputs. Findings: The results of this study found that using images in the application of compositional metafunction in learning English to improve children's abilities has a great influence, in terms of ease of learning and ease of observation. Conclusion: Based on the results presented, this study gives a new horizon that children can easily remember words in English through pictures and make motor comparisons in everyday life with the concept of cognitive development in improving memory for learning English. Keywords: compositional, images, metafunctions, children.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202214